Integrasi Model Sokongan Pemutusan di dalam Sistem Pengurusan Zakat - Shanizan Herman, Mohd. Radzi (2004)
Jabatan Zakat Negeri Kedah is an institution that manages the payment and distribution of zakat in Kedah. The purpose of this research is to build a prototype of zakat management system using decision support system characteristics. Zakat payment can be automated and the selection of asnaf candidates can be determine more effectively using zakat management system. Rule based reasoning that comprises of an IF-THEN rule with certainty factor was used to select asnaf and to determine the type of assistance qualified to be received by asnaf. The focus of asnaf selection in this research is on the poor and destitute only. Zakat management system was develop using System Development Life Cycle (SDLC) and Visual Basic programming was chosen as a tool to develop the system. System testing has proved that zakat management system can be accepted as it was successful in selecting 93.3 percent of the asnaf candidates and determine the assistance type accurately.